Modeling Combined Chemotherapy and Particle Therapy for Locally Advanced Pancreatic Cancer - Durante, Marco; Tommasino, Francesco; Yamada, Shigeru (Frontiers in Oncology, 2015)
Pancreatic ductal adenocarcinoma is the only cancer for which deaths are predicted to increase in 2014 and beyond. Combined radiochemotherapy protocols using gemcitabine and hypofractionated X-rays are ongoing in several clinical trials. Recent results indicate that charged particle therapy substantially increases local control of resectable and unresectable pancreas cancer, as predicted from previous radiobiology studies considering the high tumour hypoxia. Combination with chemotherapy improves the overall survival. We compared published data on X-ray and charged particle clinical results with or without adjuvant chemotherapy calculating the biological effective dose. We show that chemoradiotherapy with protons or carbon ions results in 1-year overall survival significantly higher than those obtained with other treatment schedules. Further hypofractionation using charged particles may result in improved local control and survival. A comparative clinical trial using the standard X-ray scheme vs. the best current standard with carbon ions is crucial and may open new opportunities for this deadly disease.